2020
DOI: 10.1158/1940-6207.capr-19-0557
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Spindle Apparatus Abnormalities in Chronic Obstructive Pulmonary Disease Cells: A Potential Pathway to Lung Cancer

Abstract: Chronic obstructive pulmonary disease (COPD) is a longterm lung disease characterized by irreversible lung damage resulting in airflow limitation, abnormal permanent airspace enlargement, and emphysema. Cigarette smoking is the major cause of COPD with 15% to 30% of smokers developing either disease. About 50% to 80% of patients with lung cancer have preexisting COPD and smokers who have COPD are at an increased risk for developing lung cancer. Therefore, COPD is considered an independent risk for lung cancer,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…It encodes a cell cycle-regulated kinase that participates in microtubule formation [ 27 , 28 ]. High-throughput data analysis demonstrated that AURKA was identified as a tumor promoter in all types of cancers [ 29 31 ]. Upregulation of AURKA has been reported in bladder cancer progression, which might be a potential therapeutic target for bladder cancer [ 32 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…It encodes a cell cycle-regulated kinase that participates in microtubule formation [ 27 , 28 ]. High-throughput data analysis demonstrated that AURKA was identified as a tumor promoter in all types of cancers [ 29 31 ]. Upregulation of AURKA has been reported in bladder cancer progression, which might be a potential therapeutic target for bladder cancer [ 32 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beas‐2B and NSCLC cells were synchronized in mitosis using a double thymidine block as detailed in our previous study. 17 Briefly, cells were treated with 2.5 mM thymidine (Cat# T1895, Sigma–Aldrich) for 24 h, incubated in a medium without thymidine for 14 h, and incubated with 2.5 mM thymidine for another 24 h, all at 37°C. After washing cells with PBS, they were then allowed to grow for 72 h. The mitotic abnormalities (multipolar spindles) were examined and compared between CSC‐treated cells and untreated (control) cells.…”
Section: Methodsmentioning
confidence: 99%
“…With acquisition settings kept constant, Z‐stacks of images at 0.2‐mm intervals were acquired, and maximum intensity projections were created. 16 , 17 , 18 , 19 …”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded at 5000 cells/well in 96‐well plates and grown for 24 h before treatment with various concentrations of AZD‐6482 and PI‐828 (Sigma‐Aldrich, # 1173900‐33‐8 and Tocris‐ 2814/1) for up to 48 h. Cell viability was assessed using the XTT assay. 29 Absorbance was read at 475 nm with a standard plate reader. The IC 50 values were calculated using GraphPad Prism software version 8.02 (GraphPad Prism, RRID:SCR_002798).…”
Section: Methodsmentioning
confidence: 99%